2016
DOI: 10.1007/s10584-016-1598-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the stationarity assumption in statistically downscaled climate projections: is past performance an indicator of future results?

Abstract: Empirical statistical downscaling (ESD) methods seek to refine global climate model (GCM) outputs via processes that glean information from a combination of observations and GCM simulations. They aim to create value-added climate projections by reducing biases and adding finer spatial detail. Analysis techniques, such as cross-validation, allow assessments of how well ESD methods meet these goals during observational periods. However, the extent to which an ESD method's skill might differ when applied to futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
107
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 21 publications
(27 reference statements)
0
107
0
Order By: Relevance
“…As the focus is on correction of spatial relationships (i.e., downscaling), Can-RCM4 outputs over the region are degraded spatially so that they are representative of a downscaling rather than pure bias correction application. Following Dixon et al (2016), simulated precipitation outputs are "coarsened" by spatially aggregating from the 0.5-deg NAM-44i grid to a coarser 2.5-deg grid and are then interpolated back onto the 0.5-deg grid. Spatial aggregation induces a fundamental mismatch in spatial scales between the model and observational fields.…”
Section: Spatial Precipitation Examplementioning
confidence: 99%
“…As the focus is on correction of spatial relationships (i.e., downscaling), Can-RCM4 outputs over the region are degraded spatially so that they are representative of a downscaling rather than pure bias correction application. Following Dixon et al (2016), simulated precipitation outputs are "coarsened" by spatially aggregating from the 0.5-deg NAM-44i grid to a coarser 2.5-deg grid and are then interpolated back onto the 0.5-deg grid. Spatial aggregation induces a fundamental mismatch in spatial scales between the model and observational fields.…”
Section: Spatial Precipitation Examplementioning
confidence: 99%
“…For example, Dixon et al (2016) found that one SD method reduced the raw GCM error in temperature by about 50% during the historical period and 30%-40% during the future. However, lurking beneath the surface of all SD methods is an implicit assumption that the transfer relationships derived from historical data are valid in a future period during which fundamental aspects of the climate system may have changed.…”
Section: Some Pitfalls In Statistical Downscaling Of Future Climatementioning
confidence: 99%
“…However, lurking beneath the surface of all SD methods is an implicit assumption that the transfer relationships derived from historical data are valid in a future period during which fundamental aspects of the climate system may have changed. In more technical terms, this is referred to as the assumption of statistical stationarity (Dixon et al 2016).…”
Section: Some Pitfalls In Statistical Downscaling Of Future Climatementioning
confidence: 99%
“…However, it also has some major drawbacks. The major limitation of the statistical downscaling approach is that it assumes the statistical relationship between the historical climate and GCMs will remain stationary for future periods under climate change [24,26,27]. Details of the limitations and strengths of the dynamical and statistical downscaling approaches are discussed in detail by Wilby and Wigely [24].…”
Section: Introductionmentioning
confidence: 99%